Regional myocardial velocity imaged by magnetic resonance in patients with ischaemic heart disease. Issue 4 (October 1994) - Karwatowski, S P; Mohiaddin, R H; Yang, G Z; Firmin, D N; St John Sutton, M; Underwood, S R
Abstract : OBJECTIVE--To assess the pattern of global and regional left ventricular long axis motion during early diastole in patients with ischaemic heart disease with and without myocardial infarction using magnetic resonance velocity mapping. DESIGN--Prospective study of 26 patients with a history of myocardial infarction (age 29-78, mean 55 years) and 21 patients with coronary artery disease without infarction (age range 39-71, mean 58 years). Values were compared with a control group (19 controls, age 35-76, mean 52 years) with a low likelihood of cardiovascular disease. RESULTS--Regional long axis velocity varied with time and position around the ventricle. All measurements were taken at the time of maximum early diastolic long axis velocity. Patients with coronary artery disease without infarction had lower values for maximum (mean (SD)) (99 (30) v 125 (33) mm/s, P < 0.05) and mean peak early diastolic wall motion (63 (13) v 82 (22) mm/s, P < 0.05) than controls. The coefficient of variation showed greater inhomogeneity of relaxation in patients than in controls (38 (18)% v 27 (10)%). All values were lower in patients with previous infarction than in patients with coronary artery disease without infarction and normal subjects. In patients with previous myocardial infarction the maximum (mean (SD)) early diastolic velocity was 80 (22) mm/s (P < 0.01 compared with controls and P < 0.05 compared with patients without infarction) and the mean (SD) velocity was 47 (18) mm/s (P < 0.01 compared with controls). The coefficient of variation was greater (52 (33)%) than for controls (P < 0.05) and patients with coronary artery disease without infarction. 18 of 26 patients with previous myocardial infarction and 13 of 21 patients with coronary artery disease without infarction had regional abnormalities corresponding to areas of fixed or reversible ischaemia on exercise electrocardiography or thallium myocardial perfusion tomography. CONCLUSIONS--Magnetic resonance velocity mapping can be used to assess regional long axis myocardial velocity. Ischaemic heart disease causes alterations in the patterns of left ventricular long axis velocity during early diastole.